The Associations Among Self-Compassion, Self-Esteem, Self-Criticism, and Concern Over Mistakes in Response to Biomechanical Feedback in Athletes - Alipour Ataabadi, Yasamin; Cormier, Danielle L.; Kowalski, Kent C.; Oates, Alison R.; Ferguson, Leah J.; Lanovaz, Joel L. (Frontiers in Sports and Active Living, 2022)
Athletes regularly face the possibility of failing to meet expectations in training and competition, and it is essential that they are equipped with strategies to facilitate coping after receiving performance feedback. Self-compassion is a potential resource to help athletes manage the various setbacks that arise in sport over and above other psychological resources. The primary purpose of this research was to explore how athletes respond to objective biomechanical feedback given after a performance. Specifically, we investigated if levels of self-compassion, self-esteem, self-criticism, and concern over mistakes were related to one another before and after a series of sprint tests interspersed with biomechanical feedback, and whether self-compassionate athletes achieved a better sprint performance after receiving and implementing biomechanical feedback. Forty-eight athletes (20 female: Mage = 19.8 years, SD = 3.1; 28 male: Mage = 23.6 years, SD = 7.8) completed online measures of self-compassion, self-esteem, self-criticism and concern over mistakes before performing four sets of 40-meter sprints. Participants received personalized biomechanical feedback after each sprint that compared their performance to gold standard results. Following all sprints, they then completed measures of self-criticism, and reported emotions, thoughts, and reactions. Self-compassion was positively correlated with self-esteem (r = .57 p < .01) and negatively related to both self-criticism (r = –.52, p < .01) and concern over mistakes (r = –.69, p < .01). We also found that athletes with higher levels of self-compassion prior to sprint performance experienced less self-critical thoughts following biomechanical feedback and subsequent sprint trials (r = –.38, p < .01). Although the results of this study provide some support for the effectiveness of self-compassion in promoting healthy emotions, thoughts, and reactions in response to sprint performance-based biomechanical feedback, a moderated regression analysis between the first and fourth sprint time variables revealed that self-compassion was not a moderator for change in sprint performance (R2 = .64, ΔR2 = .10, p > .05). These findings suggest that there are likely longer-term benefits of athletes using self-compassion to cope with biomechanical feedback, but that any benefits might be limited in a short series of sprint trials.